MORAL HUKUM DAN NILAI-NILAI KEBANGSAAN: SEBUAH REFLEKSI PEMIKIRAN BUYA HAMKA - Fokky Fuad (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2016)
ABSTRACT This study aims to analyze how Hamka’s thinking about nationality, as well as moral values in accordance with the legal system of the philosophy of Pancasila. The method used in this research is a normative legal research methods to approach concepts (conceptual approach). Hamka’s idea about national values are still relevant in developing the love for the homeland. Hamka’s thinking about nationality, religious and rejected the concept of secularization. He said God is the center of human strength established the nation. The spirit of divinity embodied in the form of patriotism needs to be instilled in every person. According to Hamka, philosophy Pancasila indicates the religious character of the Indonesian nation. Therefore, the implementation of law should be sourced from the religious philosophy of Pancasila. Recognition ofthe existence of God in the Pancasila should be realized in the form of legal which has religious values. Keywords: Hamka, legal philosophy Pancasila, moral law